2012
DOI: 10.1177/039463201202500206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-Nonylphenol and/or Diisononylphthalate on THP-1 Cells: Impact of Endocrine Disruptors on Human Immune System Parameters

Abstract: The aim of the present work is to investigate the link between two endocrine disruptor compounds (EDCs), which are chemicals that interfere with the hormone system in human and wildlife, and the human immune response through a study of their effects on the THP-1 human cell line which was used as a model for macrophages. We used two EDCs, dilsenonylphthalate (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…EDCs have been shown to alter the immune function of macrophages via decreased ERK1/2 phosphorylation . One study revealed that NP activated neutrophils through the activation of protein kinase C, p38 kinase, and ERK .…”
Section: Discussionmentioning
confidence: 99%
“…EDCs have been shown to alter the immune function of macrophages via decreased ERK1/2 phosphorylation . One study revealed that NP activated neutrophils through the activation of protein kinase C, p38 kinase, and ERK .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially very important in our modern world, where hormone-like endocrine disruptors are present in increasing number and increasing amount. There are many data that these materials can alter normal immune functions, phagocytosis included [101][102][103][104][105] and the functional alterations of phagocytosis could cause or promote diseases in the present and future human generations [106][107][108]. …”
Section: Discussionmentioning
confidence: 99%
“…Couleau et al demonstrated that several EDCs reduced phagocytosis of differentiated THP-1 cells, and disturbed TNF-a, Il-1b and IL-8 cytokine secretions, as well as decreased ERK ½ phosphorylation was associated to EDC treatments (Couleau et al, 2015). Moreover, several studies have reported similar results, showing that EDCs directly affect the innate immune system (Bennasroune et al, 2012;Ohnishi et al, 2008;Roy et al, 2012;Watanabe et al, 2003).…”
Section: Comparison Of Cnms Moamentioning
confidence: 90%